Securing Access to Counsel in Mass Arrests of Protesters: Due Process of Law and the Reconstruction of Indonesia’s New Criminal Procedure Code - Dewa Ayu Anom Wantika; Komang Widiana Purnawan (International Journal of Business, Law, and Education, 2026)
Mass arrests during public demonstrations raise a distinctive due process problem in criminal procedure: the state may lawfully maintain public order, yet coercive measures must not sever arrested persons from legal assistance at the earliest stage of custody. This article examines access to counsel in mass arrests of protesters in Indonesia through the principle of due process of law and the reform of the Criminal Procedure Code under Law No. 20 of 2025 on the Criminal Procedure Code (KUHAP 2025). Using normative legal research, the article applies statutory, conceptual, and regulatory-design approaches to constitutional norms, criminal procedure, legal aid legislation, and international standards on liberty, fair trial, and early access to legal aid. The article argues that Indonesian law formally recognizes the right to legal assistance, including through KUHAP 2025 and Law No. 16 of 2011 on Legal Aid. However, these guarantees remain framed primarily for ordinary individual criminal cases and do not provide an operational mechanism for mass arrests, where identification, notification, access to counsel, and documentation occur under compressed time and high police discretion. The article therefore proposes an Emergency Legal-Aid Protocol (Protokol Bantuan Hukum Darurat/PBHD) consisting of automated custody notification to accredited legal aid organizations and oversight bodies, mandatory delay of interrogation until counsel is present or a valid waiver is recorded, and a transparent public communication channel for families and lawyers. This protocol would shift legal aid from a passive right to an enforceable state duty and would better align protest policing with due process, accountability, and the protection of constitutional rights.